2016
DOI: 10.1161/circheartfailure.115.002698
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Magnesium Intake With Cardiac Function and Heart Failure Hospitalizations in Black Adults

Abstract: Background Little is known about the relations of magnesium intake with risk of heart failure (HF) hospitalizations, particularly in African-Americans. We hypothesize that magnesium intake relates to HF hospitalization in African-Americans. Methods and Results From the Jackson Heart Study cohort (n=5,301), we studied 4,916 African-Americans recruited during 2000–2004 in Jackson (MS), who completed an 158-item Food-Frequency Questionnaire which included dietary supplements. Total daily magnesium intake derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…However, magnesium supplementation trials on mortality outcome, largely conducted in high risk patients with acute MI have been inconclusive [ 13 ]. While one observational study has reported an inverse association between dietary magnesium intake and risk of HF hospitalisation [ 45 ], a magnesium supplementation trial has yet to be conducted in generally healthy older adults with respect to HF outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, magnesium supplementation trials on mortality outcome, largely conducted in high risk patients with acute MI have been inconclusive [ 13 ]. While one observational study has reported an inverse association between dietary magnesium intake and risk of HF hospitalisation [ 45 ], a magnesium supplementation trial has yet to be conducted in generally healthy older adults with respect to HF outcome.…”
Section: Discussionmentioning
confidence: 99%
“…MgOr is important in treating magnesium deficiency, has a cardiovascular effect, and is suited for treating heart failure. Several studies revealed that MgOr is well‐adapted by the metabolism of purine and lipoprotein in the human body .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of prospective cohort studies showed that increasing dietary magnesium intake was associated with a 22% reduction in the risk of heart HF (105). Moreover, a low dietary magnesium intake <2.3 mg/kg increased the risk for subsequent HF hospitalizations in African patients (106). Administration of magnesium showed a decrease in premature ventricular depolarization in patients with class II-IV HF (107).…”
Section: Commented [กต2]mentioning
confidence: 99%